Isotretinoin Use in Transmasculine Patients and Its Implication on Chest Masculinization Surgery: Scoping Review of the Literature - Daniel Strock; Torunn E Sivesind; Robert P Dellavalle; Gerhard S Mundinger (JMIR Publications, 2023)
BackgroundAcne often worsens in transmasculine patients who are on prolonged testosterone therapy. Isotretinoin is an oral retinoid used in the treatment of severe or refractory cases of acne, but it has the potential to cause delayed wound healing. Transmasculine patients may potentially be prescribed treatment for acne with isotretinoin while also planning to undergo chest masculinization surgery. ObjectiveThis scoping review aims to determine whether isotretinoin has a negative impact on postoperative healing in transmasculine patients undergoing chest masculinization surgery. MethodsA scoping review was performed using the PubMed and Ovid databases. A total of 16 publications were selected for inclusion. ResultsAcne tends to peak in transmasculine patients 6 months after initiation of testosterone treatment. Severe cases can be treated with isotretinoin; however, acne may recur once treatment is discontinued, given ongoing hormone therapy. There is little to no evidence in the medical literature regarding perioperative use of isotretinoin specifically among transmasculine patients undergoing chest masculinization surgery. In general, however, recent studies have found no evidence of increased hypertrophic scars or keloids in patients taking isotretinoin. ConclusionsFurther studies are required to strengthen the current evidence that suggests that isotretinoin does not need to be discontinued before or after incisional or excisional surgeries, including chest masculinization surgery in transmasculine patients.